PEMANFAATAN LIMBAH CANGKANG KERANG DARAH (Anadaragranosa) KOMBINASI EKSTRAK ETANOL DAUN SIRIH (Piper betle L.) DALAM BENTUK SEDIAAN PASTA GIGI - sukirawati, sukirawati; Sri Resky (Akademi Farmasi Yamasi Makassar, 2024)
Toothpaste is a preparation intended for cleaning and shining the surface of teeht, preventing tooth decay, improving healthy gums, providing a healthy sensation in the mouth, and controlling mouth odor. Toothpaste can be made from blood cockle shell waste and betel leaf extract. Blood cockle shell contains high levels of calcium carbonate, while betel leaf contains high antioxidants. When combined, they can strengthen and whiten teeth. The objective of this research is to create a toothpaste preperation from blood cockle shell waste combined with ethanol extract of betel leaf that meets the quality standards based on SNI 12-3524-1995, including organoleptic tests ang pH tests. This research method is an experimental laboratory study. The results showed that the combination of blood cockle shell waste and ethanol extract of betel leaf can be made in to toothpaste that meets the physical quality test requirements based on SNI, including organoleptic tests, such as green color, distinctive smell of betel leaf extract, mint flavor, slightly rough texture, and average pH value of 7.